Heat Resistance of the Powder Cobalt Alloys Reinforced with Niobium or Titanium Carbide - Cherepova, T.S.; Dmitrieva, G.P.; Nosenko, V.K. (Science and Innovation, 2024)
Heat-resistance of powder cobalt alloys at 1100 °C has been studied. These alloys have been designed for the protection of GTE blade platforms from wear and prepared by hot compaction of cobalt, chrome, aluminum, and iron powders and niobium or titanium carbides. Heat resistance of the alloys containing carbides between 30 and 70% (vol.) depends on the type of carbide: the alloys with titanium carbide have a higher heat-resistance as compared with the alloys containing niobium carbide. The most significant factor affecting the heat-resistance of alloys is porosity: as it increases the parameters decrease regardless of the type and content of carbide. The optimum composition of powder heat-resistant alloy containing titanium carbide with a melting point above 1300 °C, to be used in the aircraft engine industry has been established.